Underground life : or, mines and miners - Simonin, Louis, 1830-1886; Bristow, Henry W. (Henry William), 1817-1889 (Cambridge : Cambridge University Press, 2014)
Born in Marseilles, Louis Simonin (1830-86) became a leading mining engineer of his age. He travelled widely on government and private commissions, particularly around the United States, where he was held in very high esteem. His posthumous renown rests primarily on this substantial work on mining, first published in 1867. The book is divided into three parts, dealing with coal mining, metal mining, and the mining of precious stones. It covers metallurgy and mineralogy, the history of mining, and techniques, methods and equipment. Bringing the struggles of miners to life, and enhanced by numerous illustrations by some of the leading engravers of the day, the book is regarded as having inspired and informed Émile Zola, whose great novel Germinal (1885) depicts coal miners' lives during a strike. Simonin's work reached a wide readership in his native France, and this English translation appeared in 1869.
Author's preface -- Note by the translator -- List of coloured illustrations -- List of geological maps -- Table of illustrations -- Part I. Coal mines. 1. Coal mines - past and present ; 2. Origin of coal ; 3. History and tradition ; 4. The black country ; 5. How coal is discovered ; 6. Shafts and levels ; 7. How the coal is worked ; 8. The field of battle ; 9. Falls of roof and inundations ; 10. The perilous passage ; 11. The soldier of the abyss ; 12. Today and tomorrow -- Part II. Metalliferous mines. 1. The stages of the human race ; 2. The laboratory of nature ; 3. The princes of the mineral kingdom ; 4. The metalliferous world: Europe and Asia ; 5. The metalliferous world: America, Polynesia, Africa ; 6. Eureka ; 7. Hidden treasures ; 8. The attack on the ground ; 9. The sisters of the catacombs ; 10. Crushing and washing ; 11. The phalanx of miners ; 12. The wealth of nations -- Part III. Mines of precious stones. 1. The family of gems ; 2. In the east and under the tropics ; 3. The seekers -- Index.
Originally published: London : Chapman and Hall, 1869.
Keywords: Mineral industries; Gems; Miners